2018
DOI: 10.1016/s0140-6736(18)32158-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and cost-effectiveness of nurse-led care involving education and engagement of patients and a treat-to-target urate-lowering strategy versus usual care for gout: a randomised controlled trial

Abstract: SummaryBackgroundIn the UK, gout management is suboptimum, with only 40% of patients receiving urate-lowering therapy, usually without titration to achieve a target serum urate concentration. Nurses successfully manage many diseases in primary care. We compared nurse-led gout care to usual care led by general practitioners (GPs) for people in the community.MethodsResearch nurses were trained in best practice management of gout, including providing individualised information and engaging patients in shared deci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
252
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(264 citation statements)
references
References 32 publications
6
252
0
6
Order By: Relevance
“…The larger subsequent follow on study (n = 517) showed that 95% of patients with nurse led care and only 30% of those managed by their GP reached their SU target. 17 Pharmacist-led models have also shown some potential, with a randomised control study in California showing that over 26 weeks 35% of patients reached target SU when managed solely by a clinical pharmacist, while only 13% reached target when managed by their usual primary physician, 18 and another study set in a community rheumatology clinic showing that 82% of patients that underwent management and education by a clinical pharmacist reached target SU over a mean of 48 weeks. 19 Given these positive findings, further research into designing effective alternative models of care, and feasibility and cost-effectiveness of training nurses and pharmacists in gout care would be useful.…”
Section: Discussionmentioning
confidence: 99%
“…The larger subsequent follow on study (n = 517) showed that 95% of patients with nurse led care and only 30% of those managed by their GP reached their SU target. 17 Pharmacist-led models have also shown some potential, with a randomised control study in California showing that over 26 weeks 35% of patients reached target SU when managed solely by a clinical pharmacist, while only 13% reached target when managed by their usual primary physician, 18 and another study set in a community rheumatology clinic showing that 82% of patients that underwent management and education by a clinical pharmacist reached target SU over a mean of 48 weeks. 19 Given these positive findings, further research into designing effective alternative models of care, and feasibility and cost-effectiveness of training nurses and pharmacists in gout care would be useful.…”
Section: Discussionmentioning
confidence: 99%
“…16 In TQEH Gout Clinic, the aim is to see patients every month until target serum urate is reached. 18,19 This clinic also provided a popular platform for teaching of physician trainees and medical students, and an educative information source for general practitioners. We have shown that scheduled visits at a rheumatology gout clinic resulted in successful reduction in serum urate levels, and that patients seen monthly reached target significantly faster.…”
Section: Brief Communicationsmentioning
confidence: 99%
“…Although we did not measure cost-effectiveness, some studies suggested that treating to target can be cost-effective as this prevents loss of income, emergency room presentation and hospitalisation. 18,19 This clinic also provided a popular platform for teaching of physician trainees and medical students, and an educative information source for general practitioners. It was identified that despite the specialised clinic, the rate of withdrawal was considerable.…”
Section: Brief Communicationsmentioning
confidence: 99%
“…In addition, incorporation of Health professionals (HP) in medical information, treatment and surveillance of patients with inflammatory rheumatic diseases will improve rheumatology care and, indirectly, possibly reduce the need for rheumatologists. There is data to show that, at least in gout, nurses can be much better at providing T2T (4) treatment than GPs (16). Most of the rheumatology units work already together with qualified HPs.…”
Section: Discussionmentioning
confidence: 99%